Effects of High-Frequency rTMS on Negative Symptoms and Cognitive Function in Hospitalized Patients With Chronic Schizophrenia: A Double-Blind, Sham-Controlled Pilot Trial - Wen, Na; Chen, Lei; Miao, Xuemeng; Zhang, Min; Zhang, Yaoyao; Liu, Jie; Xu, Yao; Tong, Siyu; Tang, Wei; Wang, Mengpu; Liu, Jiahong; Zhou, Siyao; et al. (Frontiers in Psychiatry, 2021)
This study aimed to evaluate the efficacy of high-frequency repetitive transcranial magnetic stimulation (rTMS) over left dorsolateral prefrontal cortex (DLPFC) in ameliorating negative symptoms and cognitive impairments in chronic patients with schizophrenia. Fifty-two chronic patients with schizophrenia were randomly assigned to two groups: active rTMS group and sham rTMS group, with existing antipsychotic drugs combined 20 sessions of 10 Hz active/sham rTMS over DLPFC (20min/session, 5times/week). The PANSS, RBANS and SCWT were used to evaluate the clinical symptoms and cognitive functions of the patients. Our results indicated significant improvements in clinical symptoms (PANSS total and subscale scores) and cognitive functions (RBANS total and subscale scores, card 1 and card 3 of the SCWT test) (All p < 0.05) after 4-week intervention both in active and sham rTMS group. Moreover, the active rTMS group showed more effective on ameliorating negative symptoms (p = 0.002), immediate memory (p = 0.016) and delayed memory (p = 0.047) compared to the sham group. Interestingly, the decrease of PANSS negative symptom scores was significantly correlated with the increase of RBANS language scores in the real stimulation group (p = 0.046). The study found that the high frequency rTMS stimulation over left DLPFC as a supplement to antipsychotics may have potential benefits in improving clinical symptoms and cognitive impairments in chronic patients with schizophrenia.